2011
DOI: 10.1002/ccd.23159
|View full text |Cite
|
Sign up to set email alerts
|

A single center experience with same‐day transradial‐PCI patients: A contrast with published guidelines

Abstract: Using transradial approaches and structured early follow up by advance practice nurses, same-day discharge can be accomplished successfully in a broad range of patients outside of those suggested by the SCAI/ACC 2009 Consensus Document. Confirmation of these results could result in shorter hospitalizations for US patients and align advances in catheterization technology to optimize heath care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…There is an emerging body of literature7, 12, 14, 28 suggesting that SDD may be performed in more complex and elderly patients undergoing PCI, in whom complex characteristics alone are not sufficient indicators for necessitating overnight admission. Unfortunately, the existing SDD “criteria,”17 which are applicable to a lower‐risk population, are potentially too conservative to be applied in an increasingly complex elective PCI population treated in contemporary practice.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging body of literature7, 12, 14, 28 suggesting that SDD may be performed in more complex and elderly patients undergoing PCI, in whom complex characteristics alone are not sufficient indicators for necessitating overnight admission. Unfortunately, the existing SDD “criteria,”17 which are applicable to a lower‐risk population, are potentially too conservative to be applied in an increasingly complex elective PCI population treated in contemporary practice.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this guidance accurately reflects what can safely be performed in real‐world transradial PCI in 2013 is not clear, where the changing profile of modern PCI has seen an increasing workload of older, unstable and higher‐risk patients. Studies have suggested that same‐day discharge is safe in a broader range of patients with increased case complexity . No guidelines exist in the United Kingdom (UK), and although practice varies, the default in many centers is for some elective patients to stay overnight post‐PCI and, depending on their course, for convalescent ACS patients to stay at least 1 night after revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 19 articles included in this review, five were multisite and the remaining 14 studies were single-center studies. About one-third (n = 7) of the studies were conducted in the United States (Gilchrist, Rhodes, & Zimmerman, 2012;Glaser et al, 2009;Kim et al, 2013;Knopf et al, 1999;Muthusamy, Busman, Davis, & Wohns, 2013;Rao et al, 2011;Wilentz et al, 1999). The remaining 12 studies were completed in the United Kingdom (n = 4; Brewster et al, 2013;Dalby et al, 2003;Hodkinson et al, 2013;Kumar et al, 2004), Canada (Rao et al, 2011) Cohort study N = 107,018 100%…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Only one study reported addressing cardiac rehabilitation (Muthusamy et al, 2013). Cardiac education was only provided in four studies (Gilchrist et al, 2012;Knopf et al, 1999;Muthusamy et al, 2013;Wilentz et al, 1999).…”
Section: Patient Selection Patients Considered Eligible For Sddmentioning
confidence: 99%
See 1 more Smart Citation